1998
DOI: 10.1086/311099
|View full text |Cite
|
Sign up to set email alerts
|

NICMOS Imaging of the Nuclei of Arp 220

Abstract: We report high-resolution imaging of the ultraluminous infrared galaxy Arp 220 at 1.1, 1.6, and 2.22 mm with the Near-Infrared Camera and Multiobject Spectrometer on the Hubble Space Telescope. The diffraction-limited images at 0Љ .1-0Љ .2 resolution clearly resolve both nuclei of the merging galaxy system and reveal for the first time a number of luminous star clusters in the circumnuclear envelope. The morphologies of both nuclei are strongly affected by dust obscuration, even at 2.2 mm: the primary nucleus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
187
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(207 citation statements)
references
References 20 publications
18
187
2
Order By: Relevance
“…Since the absolute pointing of HST can be off by $1 00 or more (e.g., Whitmore & Zhang 2002), we compared our coordinates for seven clusters that we were able to cross-identify in common with the near-infrared HST Near-Infrared Camera and Multi-Object Spectrometer ( NICMOS) study of Scoville et al (1998), in which the coordinates were established to well within 1 00 absolute accuracy from the position of the central radio source (see their discussion). We found that it was necessary to shift the raw ACS coordinates by 3B5 in right ascension and 0B3 in a Aperture correction from a radius of 3 pixels to a large radius, interpolated from Sirianni et al (2005).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the absolute pointing of HST can be off by $1 00 or more (e.g., Whitmore & Zhang 2002), we compared our coordinates for seven clusters that we were able to cross-identify in common with the near-infrared HST Near-Infrared Camera and Multi-Object Spectrometer ( NICMOS) study of Scoville et al (1998), in which the coordinates were established to well within 1 00 absolute accuracy from the position of the central radio source (see their discussion). We found that it was necessary to shift the raw ACS coordinates by 3B5 in right ascension and 0B3 in a Aperture correction from a radius of 3 pixels to a large radius, interpolated from Sirianni et al (2005).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Near-infrared observations by Scoville et al (1998) identified eight bright star cluster candidates in Arp 220. Shioya et al (2001) combined these two sets of data to estimate ages for three of these star clusters in the range of 10-100 Myr.…”
Section: Introductionmentioning
confidence: 99%
“…This galaxy is an advanced merger system as evidenced by the large tidal tails observed in the optical (Joseph & Wright 1985;Kim et al 2002;Koda & Subaru Cosmos Team 2009) and the double nuclei (separation ∼0.98 ) observed in radio (Norris 1988), mm (Scoville et al 1997;Downes & Solomon 1998;Sakamoto et al 1999), submm (Sakamoto et al 2008) and near-IR wavelenghts (Graham et al 1990;Scoville et al 1998). These nuclei are surrounded by two counterrotating gas disks as well as a larger outer disk encompassing both (Sakamoto et al 1999;Mundell et al 2001).…”
Section: Introductionmentioning
confidence: 97%
“…The nuclei in Arp 220 are affected by a severe obscuration at 2.2 μm (Scoville et al 1998). Even at 1 mm, the dust towards the more massive western nucleus is found to be significantly optically thick (τ ∼ 1, Downes & Eckart 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(STScI) nation views of these disks, neither NGST nor the IRAC camera on SIRTF will be capable of completely penetrating these regions but will be able to detect the outer skins of star formation in these tori. The recent NIC-MOS images of the ultraluminous IR galaxy Arp 220 easily resolves the surface of the inner torus or two separate star forming regions (Scoville et al 1998). NGST, with 0.3 arcsec resolution at 10 uui, would be capable of resolving and penetrating 300 parsec dust tori at redshifts of z I".J 1.…”
Section: Studying Galaxy Formationmentioning
confidence: 99%